The INFLUENCE OF THE OPTIMAL PARENTS' INVOLVEMENT TO STUDENTS ACHIEVEMENT IN ENGLISH LEARNING - Nur Ain Hasma; Hasnawati Latief; Dzur Rif'ah Mahmudah Mahmudah (Journal of Language Testing and Assessment, 2022)
This type of research is descriptive qualitative which aims to determine the influence of parents’ involvement to students achievement in English learning at SMPN 9 Pinrang. Data acquisition by conducting interviews with parents by asking eight questions. In this study, the research subjects were parents of eight class at SMPN 9 Pinrang whose samples was used a purposive sampling technique with the characteristics of the informants parents’ educational background, type of parents’ job, and number of family members. This study was shown by four components of the influence of parents’ involvement, namely: (1) parents as caregivers and educators (2) parents as advisors (3) parents as motivators (4) parents as facilitators.The results of this study the researcher found the influence of parents’ involvement on student achievement, namely parents as educators and caregivers, parents as advisors, parents as motivators and parents as facilitators. By conducting interviews with parents of students and seeing the value of knowledge and values ​​of students' attitudes in English learning.